Using the Geology of Your Neighbourhood and City for Geoscience Outreach - Edwards, W.A. Dixon (Geoscience Canada, 2009)
Most Canadians live, work and attend school in urban areas. Your neighbour-hood has wonders such as snow-bank stratigraphy, sidewalk sedimentology, and building stone. Urban fieldtrips require little money and little time to run and they can inspire participants. An inner-city school teacher confirmed my belief in urban fieldtrips when she said, “I’ve never been able to take my students anywhere but we can now take a city bus downtown and see the world. Thank You!” So open your eyes to the grand world of geology around you. Take others on a neighbourhood trip; you will inspire, motivate and educate them. SOMMAIRE La majorité des Canadiens vivent, travaillent et étudient en milieu urbain. Votre voisinage même offre des occasions d’émerveillement comme des exemples de stratigraphie de bancs de neige, de sédimentologie des trottoirs, et de pierres de construction. Les excursions urbaines sont peu coûteuses, prennent peu de temps et peu-vent s’avérer stimulantes pour leurs participants. Une enseignante d’une école en milieu urbain a confirmé mes idées sur les excursions urbaines lorsqu’elle a déclaré, « Je n’avais jamais pu sortir mes élèves, mais maintenant, nous pouvons prendre l’autobus et voir le monde, grâce à vous. » Soyez donc à l’affût de l’univers géologique qui pointe dans votre milieu. Amener les gens de votre entourage en excursion; vous les aurez intéressés, motivés et éduqués.